IMPLEMENTASI SUPERVISI MANAJERIAL KEPALA SEKOLAH DAN KEPEMIMPINAN INSTRUKSIONAL DALAM MENINGKATKAN MUTU PROSES PEMBELAJARAN - Neliwati; Adinda Rahmah Rangkuti; Anggi Khairani; Anugrah Akbar; M. Ali Akbar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of principals’ managerial supervision and instructional leadership in improving the quality of the learning process. The study employed a qualitative approach with a descriptive design. Data were collected through observations, in-depth interviews, and documentation studies conducted at educational institutions that have consistently implemented supervision and teacher development programs. Data analysis was carried out thematically using an interactive model comprising data reduction, data display, and conclusion drawing, with data validity ensured through source and technique triangulation. The findings indicate that the systematic implementation of principals’ managerial supervision through planning, organizing, implementation, and program evaluation plays a significant role in enhancing the orderliness of instructional administration, compliance with academic standards, and teachers’ professional responsibility. In addition, principals’ instructional leadership is reflected in their active involvement in supervising the learning process, conducting classroom observations, providing constructive feedback, and facilitating teachers’ professional development. The synergy between managerial supervision and instructional leadership contributes significantly to the improvement of the quality of the learning process, making it more structured, interactive, and oriented toward continuous improvement.